NCOG-41. HISTOLOGICAL ANALYSIS OF SLEEP AND CIRCADIAN BRAIN CIRCUITRY IN CRANIAL RADIATION-INDUCED HYPERSOMNOLENCE (C-RIH) MOUSE MODEL. (12th November 2021) - Shuboni-Mulligan, Dorela; Young Jr., Demarrius; Minyety, Julianie De La Cruz; Briceno, Nicole; King, Amanda; Gilbert, Mark; Smart, DeeDee; Armstrong, Terri
Abstract: BACKGROUND: Disrupted sleep, including daytime hypersomnolence, is a core symptom reported by primary brain tumor patients and often manifests after radiotherapy. The biological mechanisms driving cranial radiation-induced hypersomnolence (C-RIH) remain unclear but we hypothesize this may result from damage to neural circuits controlling sleep behavior. We developed a mouse model of C-RIH to explore the impact of radiation on the brain: examining region-specific differences in acute DNA damage response and neuroanatomic structure. METHODS: Mice received whole brain radiation then behaviors were monitored using PhenoTyper® cages to determine optimal dose and long-term effects. To test short-term neurologic effects, brains were collected 1hr post-radiation then stained for γH2AX, a signal for DNA damage. Long-term effects were quantified 1-month post-treatment using neuroimaging to determine brain volume and T1 mapping changes in regions associated with sleep, circadian rhythms, and cognition. RESULTS: Mice displayed decreased general activity and increased daytime sleep in a dose-dependent and sustained manner. Histologic staining demonstrated that DNA damage following radiation varies across the brain, with homeostatic sleep regions and cognitive regions expressing higher levels of γH2AX than the circadian suprachiasmatic nucleus. These findings were supported by in vitro studies comparing radiation effects in SCN and cortical astrocytes using both trypan blue (F(1, 18)=235.937, p< 0.001) and clonogenic assays (F(1, 24)=40.796, < 0.001). Brain volumes were significantly smaller in irradiated than sham animals in the hippocampus (t(4)=3.833, p=0.019) and the pontine central grey (t(4)=3.504, p=0.025). T1 maps also showed significant changes in relaxation times in many cognitive regions but not sleep or circadian areas. CONCLUSIONS: These findings suggest that the homeostatic sleep region and cognitive circuits are vulnerable to radiation and may be relevant to the development of treatment plans in patients. We plan to introduce intracranial tumor to the model to evaluate the impact of timing of treatment and C-RIH on survival.